2018
DOI: 10.1016/j.jad.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of adjunct mindfulness-based intervention in treatment of bipolar disorder: A systematic review and meta-analysis

Abstract: Our meta-analysis showed significantly beneficial effects on depressive and anxiety symptoms of BD patients in within-group analysis. However, this significance was not observed in comparison with the control groups. Further clinical trials are warranted to investigate the differences in the benefits of MBIs between treatment and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 55 publications
3
40
0
6
Order By: Relevance
“…Enhancements in cognitive functions and emotional regulation, including frequency of manic episodes, were observed in patients diagnosed with bipolar disorder (BD) following regular mindfulness meditation practice. Despite the limited number of studies, MBCT seems to represent a promising treatment in BD in conjunction with pharmacotherapy . Promising but still embryonal results were found for symptom control in those with psychotic disorders …”
Section: Focus On Mental Health and Stress Management: Clinical Effecmentioning
confidence: 99%
“…Enhancements in cognitive functions and emotional regulation, including frequency of manic episodes, were observed in patients diagnosed with bipolar disorder (BD) following regular mindfulness meditation practice. Despite the limited number of studies, MBCT seems to represent a promising treatment in BD in conjunction with pharmacotherapy . Promising but still embryonal results were found for symptom control in those with psychotic disorders …”
Section: Focus On Mental Health and Stress Management: Clinical Effecmentioning
confidence: 99%
“…Yet, in spite of this, mindfulness-based treatments added to psychotherapy and the usual antidepressants 2 have been confi rmed for years now as a promising intervention adjuvant to the therapeutic approach to depression, thus improving the residual depressive symptoms after a depressive episode or preventing relapses and recurring depression in clinical populations [17,18). The potentially benefi ci al effects of mindfulness on bipolar patients suffering from anxiety and depressive disorders have recently been confi rmed [19]. The utility of mindfuln ess on severe and persistent mental disorders is also likely [19,20], since it has already been suggested that mindfulness could improve the quality of life of patients suffering from these types of disorders [21].…”
Section: Full Awareness or Mindfulness Adjuvant In The Treatment Of mentioning
confidence: 99%
“…The potentially benefi ci al effects of mindfulness on bipolar patients suffering from anxiety and depressive disorders have recently been confi rmed [19]. The utility of mindfuln ess on severe and persistent mental disorders is also likely [19,20], since it has already been suggested that mindfulness could improve the quality of life of patients suffering from these types of disorders [21]. Brief, appropriate training in mindfulness has shown positive effects in the reduction of symptoms like sadness, mental rumination, Pali -pāli, an Indic language, similar to Sanskrit used in the ancient Indo-Aryan periodis, according to theravāda tradition, the language from Magadha (an ancient kingdom in Northeast India and present-day Nepal), where Buddhism emerged.…”
Section: Full Awareness or Mindfulness Adjuvant In The Treatment Of mentioning
confidence: 99%
“…However, some recent reviews on mindfulness and bipolar disorder have exhibited mixed results. Meta‐analysis of twelve trials by Chu et al () showed significantly beneficial effects on depressive and anxiety symptoms of bipolar disorder patients in within‐group analysis. However, this significance was not observed in comparison with the control groups.…”
Section: Introductionmentioning
confidence: 99%